NGAL, cystatin C and interleukin-18 are detected Earlier than conventional biomarkers in Contrast induced nephropathy - MRS. SHOBHA M,; DR. SHANTHI NAIDU K,; DR. VIJAYARAGHAVAN R,; DR. MUJAHID M,; DR. SENTHIL KUMAR S, (International Journal of Pharma and Bio Sciences, 2017)
Stress is a leading cause of cardiovascular disorders, as more number of patients with cardiovascular diseases are undergoing interventional procedures such as cardiac catheterization; use of contrast media has become common in medical practice to diagnose the blockades of arteries. Use of these contrast media is more prone to Contrast Induced Nephropathy (CIN). Recently, NGAL (Neutrophil Gelatinase Associated Lipocaline), Cystatin C and Interleukin-18 IL-18) are emerging as novel biomarkers for the early detection of Contrast Induced Nephropathy (CIN) and has been investigated intensively. The present study proved that serum NGAL, Cystatin C and Interleukin-18 are early elevated serum markers when compared to urea and creatinine hence could serve as better markers of Contrast Induced Nephropathy (CIN). Thirty male Wistar rats were randomly distributed into 10 different cages, having 3 animals each and cages were randomly divided into 5 different groups and were injected 0.6 mL of iohexol contrast (350 mg Iodine/kg) intraperitoneally. Blood samples were obtained before and after inducing contrast and centrifuged. Results have shown that the NGAL, Cystatin C and Interleukin-18 were early to rise in serum when compared to Urea and Creatinine. The raise in levels of Interleukin-18 and Cystatin C were observed to be elevated at 3 hours and NGAL at 6 hours where as there is no change in Creatinine levels although urea has shown little change to before and after values and statistically significant P<0.05 with paired Ì” t ’ test. The present study evaluated the early raise of serum NGAL, Cystatin C and Interleukin-18 in Contrast Induced Nephropathy (CIN) when compared to urea and creatinine are delayed markers.